Institutional Diversity, Sharia Principles, and CSR Practices in MENA: A Critical Comparative Analysis - Nasrallah, Haija; Shehadieh, Hudaifah (Journal International Economic Sharia, 2024)
Objective: The aim of this research is to substantiate the nexus between institutional diversity and Sharia-compliant principles with CSR across MENA. The objective is to have a means of assessing CSR strategies across countries with different institutional environments in place, taking into consideration the political, economic and cultural aspects that have an impact.Methods: This study used mixed-methods, employing primary data through structured surveys of 300 firms in the MENA region (2020-2023) and secondary data through governance and economic indicators as well as corporate annual reports and Islamic financial services databases. Conducted data analysis using statistical methods such as regression analysis and comparative frameworks.Results: The results show that institutional factors are a significant driver of MENA CSR practices including political regimes, economic dependencies (oil vs. non-oil economies) and if the CSR practice aligns with the principles of Sharia. For countries that have centralized governance (e.g. GCC) CSR practices were more formalized and integrated into the strategic planning process, while those who have fragmented institutional environments (e.g. Egypt) focus on localized and under-coordinated approaches.Innovation: This study presents a unique comparative perspective on CSR in MENA, emphasizing the influence of Sharia on CSR alongside traditional institutional determinants, and providing fresh perspectives on continental CSR.Policy and Research Implications: An analytical implication of this study can be of importance to governments and businesses alike, as it strengthens the importance of aligning the institutional realities and cultural values with CSR strategies, which could enhance the overall sustainability and corporate governance practices in the MENA region